Study protocol for a hybrid type 3 effectiveness-implementation trial of a team-based implementation strategy to support educators’ use of a social engagement intervention - Jill Locke; Aksheya Sridhar; Wendy Shih; Stephanie Shire; Andria B. Eisman; Emily Kim; Adora Du; Christine Espeland; Connie Kasari (Implementation Science)
Abstract Background Remaking Recess (RR) is a school-based evidence-based peer social engagement intervention for autistic students. RR involves direct training and coaching with educators; however, educators face several barriers to implementation at both the individual- and organizational-levels. This protocol paper describes a multi-site study that will test whether an educator-level implementation strategy, coaching, with or without a school-level implementation strategy, school-based teams, will maximize educators’ use (fidelity and sustainment) of RR for autistic students and their peers who are socially-isolated, rejected, or peripheral and may need additional support during recess. Methods This study will employ a hybrid type-3 effectiveness-implementation trial. Fifty-five elementary schools will be recruited as well as 121 educators (e.g., classroom assistants, aides), 55 general and special educator teachers, and 83–138 other school personnel (e.g., administrators). Additionally, at least 118 autistic students and allistic or non-autistic classmates will be recruited as RR recipients. Participants will complete baseline assessments at the beginning of the year, and all schools will be provided RR training. Schools will be randomized to coaching with or without school-based teams. This study will measure RR fidelity (primary outcome), RR sustainment, as well as peer engagement, social network inclusion, and social skills (secondary outcomes). It is expected that coaching with school-based teams will improve both RR fidelity and social network inclusion, while coaching with and without school-based teams will result in improved peer engagement and social skills. Discussion Previous research has documented barriers to RR implementation at both the individual- (provider) and organization-level (school). Using multi-level implementation strategies such as coaching with school-based teams may address these barriers and support RR implementation in schools. Findings from this study may guide future efforts to scale up tailored implementation strategies for use in public school districts, with the ultimate goal of increasing intervention access and improving student outcomes. Trial registration Name of the Registry: clinicaltrials.gov. Trial Registration: Clinical Trials ID: NCT06559267 . Date of Registration: August 15, 2024. Prospectively registered.